Urban environmental problems in Ghana: a case study of social and environmental injustice in solid waste management in Accra and Sekondi-Takoradi - Baabereyir, Anthony (2009)
Unsustainable urbanization in Ghana has resulted in poor environmental conditions in urban settlements in the country. Solid waste disposal, in particular, has become a daunting task for the municipal authorities who seem to lack the capacity to tackle the mounting waste situation.